A moving track data-based method for gathering behavior prediction at early stage - Wang, Sainan; Liu, Yang; Wang, Jing; Gao, Suixiang; Yang, Wenguo (Applied intelligence (Dordrecht, Netherlands), 2021)
The early prediction and prevention of gathering events for special crowds are of great significance since the gathering behavior of individuals in special crowds may lead to illegal events or endanger public security. This paper provides an intelligent method for gathering behavior identification and gathering place predication at an early stage for special crowds based on moving track data. We firstly propose a distance-based algorithm for identifying gathering behavior and then give a fitting line-based algorithm for further finding gathering places after receiving a gathering warning. The proposed algorithms are applied to some typical cases, and the experimental results confirm the superiority, universality and efficiency of our solution method.